Principles Of Forensic Expert Activities In Ukraine And Their Implementation In Forensic Veterinary Researche - Yatsenko, Ivan (Archives of Criminology and Forensic Sciences, 2022)
The article examines the principles of forensic expert activities in Ukraine and formulates the conditions for their implementation in forensic veterinary research. It was established that the system of principles of forensic veterinary examination consists of general legal (the principle of rule of law, the principle of legality, and the principle of scientificity, systematicity, completeness and objectivity of the expert) and special ones (the principle of independence and procedural autonomy of the forensic veterinary expert, the principle of competence and certification of the forensic veterinary expert, the principle of scientific validity, objectivity, reliability, correctness and veracity of a forensic expert’s conclusion, the principle of maximum preservation of research objects, the principle of verification of the expert’s conclusion, the principle of professional ethics, the principle of personal responsibility of the forensic veterinary expert). It is claimed that non-observance of at least one of the principles of forensic veterinary examination during forensic activity leads to a violation of the entire system of principles outlined by us (general and special), as well as non-compliance with the principles and norms of both the general legal system and procedural legislation, as well as violation of specified forms of implementation of expert procedures. This, in turn, creates conditions for the recognition of the expert’s conclusion as not objective, not justified, not true, but, as evidence in the case, not admissible, and, therefore, in accordance with Art. 89 of the Criminal Procedural Code of Ukraine, it cannot be used in court proceedings, it can be referred to by an investigator or inquirer when drawing up an indictment, and a court when passing a court decision.